AJARAN SAMKHYA YOGA DALAM BHAGAVAD GITA - Ni Gusti Ayu Agung Nerawati; Ni Luh Komang Indah Sari (Widya Sandhi, 2022)
Bhagavadgita. The teachings of this samkhya provide different understandings ofpurusa and prakerti which are different, but integrated with one another. In the essenceof the Bhagavadgita which describes the philosophy of life in which every human beingwill leave or experience liberation from worldly life. So that humans must accept thechallenge between life and death and dare not to feel afraid to fight the situation becausein this world only a puppet player who is moved by the hand of God. The purpose of thisstudy is to obtain the values contained in the teachings of samkhya yoga because thisteaching is not very easy to understand and deepen understanding in order to be able tounderstand and understand the purpose of the teachings. Thus, the teachings of samkhyaprovide humans with an extraordinary understanding of life for this journey, because thislife is like a cycle of birth and death, above, below and in the middle. Therefore, the lifeof this universe no one knows how the next life will be.